2021
DOI: 10.1097/md.0000000000024748
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological significance and prognostic value of E-cadherin expression in non-small cell lung cancer

Abstract: Background: E-cadherin, a calcium-dependent cell adhesion molecule, as an important mediator of adhesion and signaling pathway, plays a key role in maintaining tissue integrity. However, the association of E-cadherin expression with clinicopathological features and prognostic value in non-small cell lung cancer (NSCLC) is still controversial. Therefore, the purpose of the study is to explore the clinicopathological features and prognostic value of E-cadherin expression in non-small cell lung cancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 42 publications
2
4
0
Order By: Relevance
“…We found that the different doses and density gradients of rhG-CSF likely played an essential role in distant organ metastases (Table 2 ). Pathological stage was also associated with metastasis following NSCLC postoperative chemotherapy (Stage IIA: HR 1.01, 95% CI 0.37–2.78, p = 0.99; Stage IIB: HR 1.90, 95% CI 1.10–3.50, p = 0.02; Stage IIIA: HR 3.52, 95% CI 1.97–6.27, p < 0.01; Stage IIIB: HR 4.39, 95% CI 1.96–9.81, p < 0.01), which is consistent with previous studies [ 12 ].…”
Section: Resultssupporting
confidence: 91%
“…We found that the different doses and density gradients of rhG-CSF likely played an essential role in distant organ metastases (Table 2 ). Pathological stage was also associated with metastasis following NSCLC postoperative chemotherapy (Stage IIA: HR 1.01, 95% CI 0.37–2.78, p = 0.99; Stage IIB: HR 1.90, 95% CI 1.10–3.50, p = 0.02; Stage IIIA: HR 3.52, 95% CI 1.97–6.27, p < 0.01; Stage IIIB: HR 4.39, 95% CI 1.96–9.81, p < 0.01), which is consistent with previous studies [ 12 ].…”
Section: Resultssupporting
confidence: 91%
“…Sincerely, we found the different dosage and density gradients of rhG-CSF likely play an essential role in distant organ metastases (Table 2). Besides, clinical-stage were also associated with metastasis following NSCLC postoperative chemotherapy (Stage : HR 1.80, 95 % CI 1.02-3.19, p=0.04, Stage : HR 3.61, 95% CI 2.04-6.36, p<0.01), that is consistent with previous studies [12] .…”
Section: Prognostic Factors For Metastasissupporting
confidence: 91%
“…Fifteen pathways related to cell adhesion and immune and inflammatory responses were selected (Supplementary Table S2). Some cell adhesion molecules, which have been identified as tumor suppressor genes, are associated with a better prognosis in cancers (Sawada et al, 2020;Chao et al, 2021). Immune-and inflammation-related pathways such as "natural killer cell-mediated cytotoxicity," "B cell receptor signaling pathway," "cytokine-cytokine receptor interaction," "chemokine signaling pathway," "JAK-STAT signaling pathway," "T cell receptor signaling pathway" and "FC gamma R mediated phagocytosis," were also enriched in the LRMP high expression group.…”
Section: Discussionmentioning
confidence: 99%